Enfermedades del frijol (Phaseolus vulgaris L) - Castaño, J.J. (International Center for Tropical Agriculture, 1979)
The symptomatology and control of the principal bean diseases in Colombia are discussed, classifying them as (1) biotic: root rot caused by fungi, bacteria and nematodes; foliage diseases - anthracnose, rust, angular leaf spot, powdery mildew, Ascochyta leaf spot, gray spot, floury leaf spot, pod scorch caused by Diaporthe phaseolorum, white mild, halo blight, common and fuscous blights. (2) viral: BCMV and BGMV; (3) abiotic disorders: (a) physicogenic: natural deficiencies, sunscald and damage caused by high winds and excess drought; and (b) enzymatic: phytotoxemias and phytotoxicities; and (4) diseases during transportation and storage. (CIAT)